2003
DOI: 10.1359/jbmr.2003.18.9.1682
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Bone Mineral Density and Bone Histology in Thalassemia

Abstract: This study demonstrated that there was extensive iron staining on trabecular surface and marked reduction in trabecular bone volume without significant alteration in bone formation and bone resorption rates as well as significant reduction in bone mineral density in 18 thalassemic patients. Serum IGF-I was reduced and may modulate the reduction of bone mass.Introduction: Bone histomorphometric studies in thalassemia to show alterations in bone histology and their relationship to biochemical parameters are very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
2
34
2
Order By: Relevance
“…Histomorphometry studies have revealed that increased osteoid thickness, increased osteoid maturation and min-eralization lag time, which indicate impaired bone matrix maturation, and defective mineralization is present in children and adolescents with TM (33). In addition, iron deposits appeared along mineralization fronts and osteoid surfaces, whereas focal thickened osteoid seams were found together with focal iron deposits (33,43). Finally, dynamic bone formation histomorphometry studies established reduced bone formation rate in TM patients (33).…”
Section: Acquired Factorsmentioning
confidence: 99%
“…Histomorphometry studies have revealed that increased osteoid thickness, increased osteoid maturation and min-eralization lag time, which indicate impaired bone matrix maturation, and defective mineralization is present in children and adolescents with TM (33). In addition, iron deposits appeared along mineralization fronts and osteoid surfaces, whereas focal thickened osteoid seams were found together with focal iron deposits (33,43). Finally, dynamic bone formation histomorphometry studies established reduced bone formation rate in TM patients (33).…”
Section: Acquired Factorsmentioning
confidence: 99%
“…thalassemic mice with heterozygous b-globin gene deletion, bone loss as determined by microcomputed tomography was observed in both trabecular and cortical parts of long bone, presumably due to a decrease in the osteoblast-mediated bone formation (Vogiatzi et al 2010). In contrast, the osteoblast surface, bone formation rate, osteoclast number and osteoclast surface of the transiliac crest biopsy were not altered in b-thalassemia/hemoglobin E patients as compared to the control subjects with normal genotype (Domrongkitchaiporn et al 2003), suggesting that bone loss in this genotype might not have resulted from the suppressed bone formation and/or accelerated bone resorption. Moreover, the histological changes in trabecular microstructure in other genotypes, such as b IVSII-654 , have not been demonstrated; however, trabecular osteopenia is anticipated.…”
mentioning
confidence: 92%
“…Domrongkitchaiporn et al 2003 by using trans-iliac crest bone histomorphometry showed that iron was extensively deposited on the trabecular surface, and that trabecular bone volume was markedly decreased in b-thalassemia/hemoglobin E patients. In th3/?…”
mentioning
confidence: 99%
“…Several previous studies showed lower BMD in thalassemic patients [22], [23], [24], [25], [26]which due to their low physical improvement which affected by iron overload and iron chelation that can affect the liver and the endocrine system.…”
Section: Resultsmentioning
confidence: 99%